PENATAAN ARSIP DINAMIS INAKTIF DI BADAN KELUARGA BERENCANA PEMBERDAYAAN MASYARAKAT DAN PEMBERDAYAAN PEREMPUAN KABUPATEN SLEMAN - , NUDZULA RHOMADLONA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This Final Paper titled âThe Arrangement Of Inactive Records At Badan Keluarga Berencana, Pemberdayaan Masyarakat, dan Pemberdayaan Perempuan Kabupaten Slemanâ is the result of the data that writer gather during the practices in field. The purpose of this field practices in to know the structure of inactive records in Badan Keluarga Berencana, Pemberdayaan Masyarakat, dan Pemberdayaan Perempuan Kabupaten Sleman. The method that has bean writer use in the field practices are interview, observation-participation, and library study. The purpose of the interview is to complete the data that has been received before. When doing the field practice, the direct observation is used by the writer to see the inactive records. With this method, writer can get a direct observation to the inactive records and get a concrete data that is related to the instance then know the knowledge of records to applicate the facts of that instance. After collecting the data, finally writer can make a conclusion. Which is the organizer and the inavtive records in Badan Keluarga Berencana, Pemberdayaan Masyarakat, dan Pemberdayaan Perempuan Kabupaten Sleman is not appropriate yet with the correct records knowledge because of the facility, human recources, and the medium is that still not enough.